Changes in fat mass and fat-free-mass are associated with incident hypertension in four population-based studies from Germany. (1st January 2019) - Ittermann, Till; Werner, Nicole; Lieb, Wolfgang; Merz, Benedikt; Nöthlings, Ute; Kluttig, Alexander; Tiller, Daniel; Greiser, Karin H.; Vogt, Susanne; Thorand, Barbara; Peters, Annette; Völzke, Henry; et al.
Abstract: Background: We estimated the association of changes in body weight, waist circumference (WC), fat mass (FM) and fat-free mass (FFM) with changes in blood pressure and incident hypertension using data from four German population-based studies. Methods: We analyzed data from 4467 participants, aged 21 to 82 years not taking antihypertensive medication and not having type 2 diabetes mellitus or a history of myocardial infarction at baseline and follow-up, from four population-based studies conducted in Germany. Body weight, WC, and blood pressure were measured at baseline and follow-up (median follow-up of the single studies 4 to 7 years). FM and FFM were calculated based on height-weight models derived from bioelectrical impedance studies. Hypertension was defined as systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg. Confounder-adjusted linear and logistic regressions were used to associate changes in anthropometric markers with changes in blood pressure, incident hypertension, and incident normalization of blood pressure. Results: In a pooled dataset including all four studies, increments in body weight, WC, FM, and FFM were statistically significantly associated with incident hypertension and changes in systolic and diastolic blood pressure over time. Decreases in body weight, FM, and FFM were significantly associated with incident normalization of blood pressure. Conclusions: Our data suggests that the well-established association between obesity and blood pressure levels might be more related to body composition rather than to total body weight per se. Our findings indicate that gaining or losing FFM has substantial impact on the development or reversion of hypertension. Highlights: Changes in body composition are more relevant for development or reversal of hypertension than total body weight per se. Gaining fat-free mass has substantial impact on increase of blood pressure levels. Losing fat-free mass has substantial impact on decrease of blood pressure levels.